The effect on birth pain and process of the freedom of movement in the first stage of labor: a randomized controlled study - YILDIZ, HATİCE (My University, 2022)
Objective: To determine the effect of freedom of movement implemented in the dilatation stage, which is the first stage of labor, on the labor process in pregnant women who will give their first birth.Methods: This study was designed as a randomized controlled trial. The study consisted of 70 primiparous women, including 35 in the study group (SG) and 35 in the control group (CG). Freedom of movement was provided to the study group in the first stage of labor. Data were collected using a Personal Information Questionnaire, a Labor Assessment Form, and the Visual Analog Scale (VAS) for perceived pain.Results: The SG was observed to be walking when dilatations were 4-7 cm and mostly squatting when 8-10 cm (94.2%). The level of effacement, frequency of contraction, and descent of the fetal head were faster (p<0.01), and total dilatation, expulsion, placental expulsion, and total labor and delivery time were shorter in pregnant women in the SG (p<0.001). After delivery, the SG had shorter initial contact with their babies and first breastfeeding time, and the total 24-hour postpartum hemorrhage was less (p<0.001). When there was no freedom of movement during labor, the total dilation time (OR=2.41), expulsion time (OR=1.25), placental expulsion time (OR=1.16), total delivery time (OR=2.76), the VAS score at 6 - 7cm dilatation time (OR=2.48), and first breastfeeding time (OR=1.15) were found to increase (p<0.05-0.01).Conclusion: The freedom of movement allowed at the first stage of labor was observed to reduce perceived labor pain, the process of labor and delivery time, the volume of postpartum hemorrhage, and the time of the first contact with the infant and the first breastfeeding.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Labor; delivery; stage; birth process; freedom of movement; effect; HEALTHY BIRTH; CARE; POSITIONS; DELIVERY; 2ND-STAGE